Implementation Fun Teaching In Online Qur'an Learning During Pandemic At Madrasah Ibtidaiyah Al-Hikmah - Aqib, Mohammad Auzai; Laily, Mamba‘atul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Long distance learning activities (PJJ) have made some students feel bored. Innovation is needed so that students can grow motivation to learn and get excited again in studying the material of the Koran even though they are online. The purpose of writing this article is to (1) determine the implementation of the fun teaching method in online qur'an learning; (2) Knowing the results of student achievement after the fun teaching method was applied; and (3) Knowing students' responses to qur'an subjects using the fun teaching method. This research is a qualitative descriptive study. While the data sources come from observations, interviews, and documentation. The analysis technique using Miles and Hubberman is in the form of reduction, categorization, data presentation, and drawing conclusions. Implementation of Fun Teaching on Qur'an Hadith material for class IV by using the WhatsApp group method. This online fun teaching method improves the learning achievement of MI Al-Hikmah's qur'an, that is, the average value of student learning achievement only reaches 58%, after the application of the fun teaching method it increases to 81% while for the response aspect students get a good response. very positive.